Frequencies of-308G/A (TNFA) and-509C/T (TGFB1) polymorphisms in sickle cell anemia patients from Brazil - Torres, L. S. [UNESP]; Belini Junior, E. [UNESP]; Silva, D. G. [UNESP]; Lobo, C. L.; Ruiz, M. A.; Bonini-Domingos, C. R. [UNESP] (Funpec-editora, 2013)
Sickle cell anemia is an affection that causes chronic inflammation, with consequences for vaso-occlusion, oxidative stress and cytokine production. Genetic polymorphisms in markers involved in this process can modulate the inflammatory response, including polymorphism -308G/A of TNFA (tumor necrosis factor alpha) and -509C/T of TGFB1 (transforming growth factor beta 1), reported to increase TNF-alpha and TGF-beta 1 production, respectively. Changes in the cytokine balance are important risk Factors for clinical events; consequently, we examined the frequencies of these polymorphisms in 240 Brazilian sickle cell anemia patients from southeast Brazil. PCR-RFLP was used to detect these polymorphism. The -509C/T (TGFB1) polymorphism was more frequent than -308G/A (TNFA), with allelic frequency of 0.3 for the mutant allele T (TGFB) agaist 0.1 for the mutant allele A (TNFA). These allelic frequencies are similar to those known from populations with ethnicity similar to the Brazilian population. Inheritance of these polymorphisms does not seem to be associated with that of the Hb S mutation; however, this information could be useful in analyses of specific clinical characteristics of sickle cell anemia.
Keywords: Allelic frequency; Genetic polymorphism; PCR-RFLP; Sickle cell disease; SNPs; Hemoglobin S